Sistem Pendukung Keputusan Pemberian Bantuan Kepada Nelayan Menggunakan Metode Simple Additive Weighting (SAW) - Panggabean, Anastasya; Siswanto, Siswanto; Sapri, Sapri (Jurnal Media Infotama, 2024)
Department of Marine Affairs and Fisheries of Bengkulu Province is one of the government agencies in Bengkulu Province. At Department of Marine Affairs and Fisheries of Bengkulu Province there are several assistance programs from the government, one of which is the provision of assistance to fishermen which is carried out every year, and the processing of recipient data is still done manually. The decision support system for providing assistance to fishermen can assist the Department of Marine Affairs and Fisheries of Bengkulu Province in processing data on providing assistance to fishermen and providing information output from the results of data processing, and can help make decisions to determine the provision of assistance to fishermen which is carried out annually based on the results of an assessment using the Simple Additive Weighting (SAW) method. Based on test data as many as 10 groups of fishermen after being processed through the SAW Method, the final results obtained are 5 groups of fishermen who are eligible to receive assistance, including Sabar Menanti, Pulau Indah, Taman Sari, NPM I, and Burung Camar Dua which are recommended to get assistance provided by the government. Based on the black box testing that has been done, it is found that the functionality of the application runs as expected and the application is able to display the results of the fishermen group assessment through the SAW Method stages.